Implementation of Barangayan para sa Bawat Bata Bumabasa Reading Program of the Selected Elementary Schools in Rodriguez, Rizal - Melanie M. Goron, MAEd; Ardrian D. Malangen, MAEd (Research Parks Publishing LLC, 2023)
Children's future success is contingent upon their capacity to read and understand what they read. Reading is the foundation for all other study skills. Due to the lockdown and quarantine restrictions brough by the pandemic, the program faced challenges among the school, parents, students, and to the stakeholders. Furthermore, the purpose of the study is to determine the extent of the Implementation of Barangayan para sa Bawat Bata Bumabasa (BR-B4) Reading Program of the Selected Elementary Schools in Rodriguez Sub-Office. It will scrutinize the implementation of the BRB4 in terms of reading materials, teaching materials used, the learning schedule, and the funding mechanism. The study utilized descriptive correlational design and used survey questionnaire as the main data-gathering instrument, which was floated to a total of 157 teachers in different schools. The results of the study shows that BRB4 reading program in the selected elementary schools is “Extremely Implemented”, the challenges encountered in the implementation of the BRB4 reading program are sometimes experienced and no significant differences when grouped according to profile. Thus, the school must take action to give teachers, students, and parents with assistance in their areas of difficulty in the implementation of the reading program and teachers are encouraged to work collaboratively with parents to foster genuine love for reading among pupils.